(untitled) (Research, Society and Development, 2020)
Lipases are catalysts that have great potential for industrial applications (recent or consolidated) that include the food, pharmaceutical, leather, bioremediation area of oils and fats and biodiesel production. In this context, microbial lipases have attractive characteristics and stand out as the main source of these enzymes. Among the most promising microorganisms it is possible to point out filamentous fungi as excellent producers of lipases, since many studies on these lipases and their characteristics have been carried out. Considering the need to identify possible trends and gaps in studies on the biochemical characteristics of lipases produced by filamentous fungi this work aimed to contribute to knowledge through a literature review about the biochemical characterization of lipases produced by the genera Aspergillus, Penicillium and Trichoderma aiming to be employed as a source comprehensive information for researchers in the area. The Databases Web of Science, ScienceDirect and Google Scholar were used as a source, seeking original articles published from2010-current, in English or Portuguese languages and with the keywords defined in line with the main theme of this study and possible related areas. The results indicated that the genus Aspergillus is the most studied in the biochemical characterization studies of lipases and that there is possibly a research gap for the biochemical characterization of lipases produced by the genus Trichoderma and intracellular lipases, indicating a niche of research with potential to be explored. The areas of lipase applications most frequently cited by the authors of the studies analyzed are the formulation of detergents, production of biofuels and bioremediation/treatment of industrial effluents, indicating that these areas may be prioritized in future research. It is concluded that por more than the systematic review of the literature performed provides a range of useful knowledge for researchers it is necessary to be careful, because the results found may not take into account articles that are not indexed in the databases consulted.